FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF HAND SANITIZER ETHANOL EXTRACT OF BASIL (Ocimum Sanctum. L) AGAINST Escherichia coli dan Streptococcus Aureus - Nurfiddin Farid; Nurhikma Awaluddin; Suhartina Hamzah; Muhammad Yusuf; Rahmania Rahmania (Politeknik Kesehatan Makassar, 2020)
Basil leaves (Ocimum sanctum L) Against to inhibit the growth of Escherichia coli and Staphylococcus aureus bacteria to increase its effectiveness, it is made in practical and easy-to-use preparations. One of the effective dosage forms for topical use is Hand Sanitizer. The factor that influences the quality of gel preparations is Carbopol as a gelling agent. To know the antibacterial effect and ethanol extract concentration of basis leaves (Ocimum sanctum L). preparation of Hand sanitizer, in which the selection and type of carbopol concentration will determine the stability of the gel formed. Basil leaf extract was obtained by maceration method using 96% ethanol solvent. The product is formulation in the form a gel Hand sanitizer with the addition of carbopol as a gelling agent with a concentration of 1,5% this type of research is laboratory Experiment with Stability Test, Organoleptic Test, pH, Homogeneity and Scattering power and Antibacterial Test on Escherichia coli and Staphylococcus aureus. For testing antibacterial activity the method used is the diffusion method. Form the research results obtained antibacterial Hand sanitizer preparations with concentration of 1%, 3% and 5% showed changes in odor , color and shape before and after storage at pH 4,8- 6,4. Organoleptic testing showed no changes in odor, color and shape before and after accelerated storage. pH testing shows charges before and after storage are caused by temperature light factors. Homogeneity testing showed no changes before and after storage. Scatter tests indicate changes before and after storage caused by temperature light factors. Antibacterial activity test shows that the formulation of Hand sanitizer ethanol extract of basil leaves (Ocimum sanctum L) with a concentration of 1%, 3% and 5%. can inhibit the growth of Escherichia coli and Staphylococcus aureus with Medium -Strong inhibitory zones. From the results of research conducted it was concluded that the antibacterial Hand sanitizer ethanol of basis was physically and chemically stable for Organiletic, pH, Homogeneity and Scattering effects.